Evaluación de porcentajes de inulina y AGT-800 en las características fisicoquímicas del yogur batido tipo I utilizando sólidos no grasos - Cuellar Zambrano, Carlos Alfredo (2022)
The purpose of this research was to evaluate the percentages of inulin and AGT -800 (stabilizer based on modified starch, gelatin and guar gum for yogurt) on the physicochemical characteristics of type I whipped yogurt, using non-fat solids. A bifactorial completely randomized design (CRD) with six treatments and three replicates was used. Factor A: Inulin and AGT-800; Factor B: percentages of stabilizers at 1%, 2% and 3% respectively, 3 replicates were carried out for each treatment, the experimental unit was 4000 g. The variables measured in terms of physicochemical characteristics were: Viscosity, pH, syneresis, Brix degrees, total solids and acidity, whose results were subjected to Shapiro-Wilks normality test and homogeneity test called Levene's test; resulting in factor B with incidence in the ºBrix variable while factor A presented significance in the other variables The results showed that the best treatment was T2 with 2% inulin. On the other hand, to evaluate the microbiological quality, microbiological analyses of total coliforms, E. coli count and mold and yeast count were carried out according to INEN 2395 and the results obtained show that there is no presence of total coliforms and the same for Escherichia coli. Finally, a sensory analysis was carried out with 50 untrained judges and the results obtained were analyzed by means of the Friedman test, where it was established that T2 with 2% inulin was the most acceptable.